148k views
5 votes
21. Given that f(x)= x^3– x² + 5x and g(x)= x^3 +5x^2 –2 determine
(g-f)(x)

1 Answer

6 votes

Answer:

(g - f)(x) = 6x² - 5x - 2

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = x³ - x² + 5x

g(x) = x³ + 5x² - 2

(g - f)(x) is g(x) - f(x)

Step 2: Evaluate

  1. Substitute: (g - f)(x) = x³ + 5x² - 2 - (x³ - x² + 5x)
  2. Distribute -1: (g - f)(x) = x³ + 5x² - 2 - x³ + x² - 5x
  3. Combine like terms: (g - f)(x) = 6x² - 5x - 2
User Shaft
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.